Generating regenerative agriculture - Garbisu, Carlos; Unamunzaga, Olatz; Alkorta, Itziar (Frontiers in Sustainable Food Systems, 2025)
Despite its being still a somewhat vague concept, regenerative agriculture has progressively been gaining momentum and popularity in recent years. While discussing the meaning of the term regenerative agriculture, we propose to link regenerative agriculture with the safe and just Earth system boundaries framework, as the basis for the generation of a paradigm that could robustly ground an appealing regenerative narrative that could nourish the vocation of a new generation of farmers and agronomists. The evaluation of the safe and just Earth system boundaries accounts for Earth system resilience and human well-being in an integrated framework, which is precisely what sustainable agriculture is all about. Our proposal connects the small (the farm) with the colossal (the Earth) in an attempt to confront one of the main sources of criticism for agriculture, i.e., its global environmental impact. The idea is to define the performance of regenerative agriculture in terms of its positive influence on the eight safe and just Earth system boundaries through its sustainable contribution to a highly-productive, environmentally-sound, nature- and biodiversity-respectful, socially-responsible, and ethically-committed agriculture. Finally, we propose a definition of regenerative agriculture that incorporates the abovementioned proposal.